2010
DOI: 10.1002/pssb.200945594
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and physical properties of cylindrite micro tubes and lamellae

Abstract: The natural semiconductor cylindrite FeSn 4 Pb 3 Sb 2 S 14 was synthesised by chemical vapour transport (CVT). Crystals with lamellar shape and cylindrical morphology could be deposited on substrates. The endothermic reactions responsible for material transport were simulated by means of thermodynamic modelling. Cylindrite belongs to the class of misfit layered compounds, where its modulated incommensurate crystal structure is based on the regular alternation of two types of layers. The so called T-and H-slab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, the growth conditions to reproduce the structure of cylindrite can be replicated in the laboratory to synthesize artificial crystals with cylindrite structure but with user-tailored composition. [41,42] Figure 1 shows a simplified representation of the crystal structure of cylindrite where for the sake of simplicity substitutional Fe, Sb and Sn atoms are not displayed. Figure 2a shows an optical image of cylindrite mineral displaying its characteristic appearance with clusters of small diameter (< 1 mm) and long (~ 3 -5 mm) cylinders.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the growth conditions to reproduce the structure of cylindrite can be replicated in the laboratory to synthesize artificial crystals with cylindrite structure but with user-tailored composition. [41,42] Figure 1 shows a simplified representation of the crystal structure of cylindrite where for the sake of simplicity substitutional Fe, Sb and Sn atoms are not displayed. Figure 2a shows an optical image of cylindrite mineral displaying its characteristic appearance with clusters of small diameter (< 1 mm) and long (~ 3 -5 mm) cylinders.…”
mentioning
confidence: 99%
“…This feature is originated by a phase segregation of the two crystalline phases during the rock formation. Interestingly, the growth conditions to reproduce the structure of cylindrite can be replicated in the laboratory to synthesize artificial crystals with cylindrite structure but with user-tailored composition [41,42]. Figure 1 shows a simplified representation of the crystal structure of cylindrite where for the sake of simplicity substitutional Fe, Sb and Sn atoms are not displayed.…”
mentioning
confidence: 99%
“…The vdW heterostructures present unique electronic properties due to the incommensurate and modulating nature of their structural configurations along the crystallographic a - and b -directions. Despite their fascinating and attractive properties, only a few groups have so far succeeded in the synthesis of such heterostructures [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The structure is composed of stacked, weakly coupled [Pb 2 BiS 3 ] layers and [AuTe 2 ] sheets. Magneto-transport measurements showed that [Pb 2 BiS 3 ]­[AuTe 2 ] is a multiband semimetal with strong spin–orbit coupling. , Actually, in nature, there are several other interesting 2D materials, such as the so-called cylindrite (FeSn 4 Pb 3 Sb 2 S 14 ), abramovite (Pb 2 SnInBiS 7 ), merelaniite (Mo 4 Pb 4 VSbS 15 ), levyclaudite (Pb 8 Sn 7 Cu 3 (Bi,Sb) 3 S 28 ), and jaszczakite ([(Pb,Bi) 3 S 3 ]­[AuS 2 ]), to name a few. Recently, it was demonstrated that the mineral franckeite can be exfoliated into a few layers toward efficient photodetectors .…”
Section: Introductionmentioning
confidence: 99%